Platelet abnormalities in autoimmune thyroid diseases: A systematic review and meta-analysis - Cao, Yu-tian; Zhang, Kai-yu; Sun, Jing; Lou, Yan; Lv, Tian-su; Yang, Xinyi; Zhang, Wen-hui; Yu, Jiang-yi; Wu, Qi-biao; Zhou, Xi-qiao (Frontiers in Immunology, 2022)
Background: Some degree of platelet index abnormality has been found clinically in the autoimmune thyroid disease (AITD), but the findings are not uniform. Methods: The PubMed, Web of Science, Cochrane Library, and Embase databases were searched for relevant articles published up to August 16th, 2022, with no restrictions on the language of the articles. Reference lists of eligible articles were also searched. A random effect model was used to pool the standardized mean difference (SMD) and 95% confidence interval (95% CI) of platelet count (PLT), mean platelet volume (MPV), and platelet distribution width (PDW) between AITD patients and healthy controls, and subgroup analyses were performed. Results: A total of 19 articles with 6173 people (3824 AITD patients and 2349 healthy people) were included in the meta-analysis. The results showed that PLT and MPV values were significantly increased in AITD patients when compared with healthy people (SMD: 0.164, 95% CI: 0.044 to 0.285; SMD: 0.256, 95% CI: 0.013 to 0.500), while no significant difference was found in PDW between the AITD group and the control group (SMD: 0.060, 95% CI: -0.164 to 0.284). Subgroup analysis according to disease type and thyroid function revealed that for PLT, this difference was only found in the Hashimoto’s thyroiditis (HT) and hypothyroid groups, but not in the Graves’ disease (GD) and hyperthyroid groups. For MPV, the results were the opposite of those for PLT: MPV was significantly higher in the GD, hyperthyroid, and euthyroid groups than in the control group, but not in the HT and hypothyroid groups. Sensitivity analysis showed that the stability of the pooled MPV was not good. No publication bias was found. Conclusions: PLT and MPV are significantly elevated in patients with AITD, with PLT being more significantly elevated in HT and hypothyroidism, and MPV being more significantly increased in GD and hyperthyroidism. Appropriate clinical attention can be paid to the thyroid function of patients when abnormal platelet indices are found, and conversely, the consequences of abnormal platelet parameters such as elevated MPV lead to an increased occurrence of cardiovascular events, which should also be addressed in the AITD population.